Male sexual dysfunction, leptin, pituitary and gonadal hormones in Nigerian males with metabolic syndrome and type 2 diabetes mellitus (2016)
Background: Pituitary and gonadal dysfunctions resulting from increased adiposity leading to disturbances of sexual and reproductive functions have been reported in males with metabolic syndrome (MS) and type 2 diabetes mellitus (DM2). The aim of this study was to evaluate sexual dysfunction, leptin, and reproductive hormones in Nigerian males with MS and DM2. Methods: Participants were 104 men (34 males with DM2, 17 men with MS and 53 men with normal body mass index (18.5-24.9 Kg/m2) without MS (controls)). The International Diabetes Federation (2005) criteria were used for MS diagnosis. Reproductive history, anthropometry, blood pressure (BP) and 10 ml fasting blood samples were obtained by standard methods. Fasting plasma glucose, total cholesterol, triglycerides and high density lipoprotein cholesterol were determined by enzymatic methods while low density lipoprotein cholesterol was calculated. Leptin, follicle stimulating hormone (FSH), luteinising hormone (LH), prolactin, testosterone and oestrogen were determined by enzyme immunoassay (leptin by Diagnostic Automation, Inc.; others by Immunometrics (UK) Ltd.) while oestrogen-testosterone ratio was calculated. Data analyzed using ANOVA, Chi square and multiple regression were statistically significant at p<0.05. Results: Testosterone was significantly lower in MS than controls while oestradiol and ETR were significantly higher in MS compared with controls and DM2 group (p<0.05). ETR significantly predicted testosterone in all groups (p<0.05). Significantly lower libido was observed in men in MS than controls and DM2 groups (p<0.05). Conclusion: Sexual and reproductive dysfunction may be related to increased conversion of testosterone to oestrogen in increased adipose mass in men with metabolic syndrome and type 2 diabetes mellitus.